Factors influencing farmers' use of the warehouse receipt system in Indonesia. Issue 4 (5th August 2019) - Gunawan, Endro; Kuwornu, John K.M.; Datta, Avishek; Nguyen, Loc T.
Abstract : Purpose: The purpose of this paper is to examine the factors influencing Indonesian farmers' use of the warehouse receipt system (WRS) and their choice of private and public warehouses. Design/methodology/approach: Primary data were collected through questionnaires administered to 500 farmers in two districts, Subang and Cianjur, in West Java Province in Indonesia. Binary logit regression was employed to examine the factors influencing farmers' use of the WRS. Binary and bivariate probit regressions were employed to determine the factors influencing farmers' choice of private and public warehouses. Findings: The empirical results of the binary logit regression revealed that age, land ownership, selling price, the use of the warehouse receipt as collateral security and the availability of transportation facility positively influenced farmers' use of the WRS, whereas education, income, farm profit and participation in farmers' group negatively influenced farmers' use of the WRS. The results of the binary probit regressions revealed that profit, availability of insurance and processing facility positively influenced the farmers' decision to use the private WRS, whereas education, production, selling price and distance from the farm to the warehouse negatively influenced farmers' decision to use the private WRS. Age, education, selling price and distance from the farm to the warehouse positively influenced the farmers' decision to use the public WRS, whereas production and availability of processing facility negatively influenced the decision of farmers to use the public WRS. Practical implications: This study highlights the importance of education and government assistance regarding the provision of facilities and price indemnified insurance for successful implementation of the WRS. Originality/value: This study provides an empirical contribution to the existing literature on the development of WRS in Indonesia. In terms of methods of analysis, previous studies used purely qualitative and descriptive methods, whereas this study employed econometric techniques (i.e. binary logit, binary probit and bivariate probit regressions) to examine the WRS in Indonesia. In addition, whereas previous studies explored the WRS in general, this study investigated the farmers' use of the public and private warehouses in addition to exploring the WRS in general. Finally, the finding that the average annual profit of non-users was significantly higher than that of the users of the WRS is striking, and this could be attributed to the current challenges of the implementation of the WRS, including high transportation and warehouse rental costs.